Laminar forced convection effectiveness of Al2O3–water nanofluid flow in a circular tube at various operation temperatures: Effects of temperature-dependent properties. (September 2016) - Ho, C.J.; Chang, C.Y.; Cheng, C.Y.; Cheng, S.J.; Guo, Y.W.; Hsu, S.T.; Yan, Wei-Mon
Highlights: Effects of variable properties of nanofluid on laminar heat transfer in a circular tube were examined numerically. The predicted results with constant and variable properties are compared in details. The Al2 O3 –water nanofluid can enhance thermal performance under elevated temperature operations. Abstract: In this paper, effects of temperature-dependent thermophysical properties on laminar forced convection effectiveness of Al2 O3 –water nanofluids in a circular tube imposed to a constant heat flux are investigated numerically. The numerical study is supplemented with a scale analysis based on the integral energy equation. The analysis is conducted for various inlet temperatures and considering two cases for properties including (i) constant-properties, and (ii) temperature-dependent properties. The simulated results are presented for three different concentrations of nanofluids i.e. 0%, 5%, and 9%, volume flow rates in the range of 24–180 cm 3 /min which correspond with Reynolds numbers between 120 and 2000, heat fluxes between 5.51 × 10 2 and 1.23 × 10 4  W/m 2, and various inlet temperatures in the range of 25–50 °C. The effects of various inlet temperatures of nanofluids and different thermophysical models on the local and average Nusselt numbers in the tube have been investigated in details. It is found that with an increase in both nanofluid concentration and temperature rise in the heated section, the effects of inlet temperature and thermophysical properties on the Nusselt number are more pronounced.